Incidence of tooth sensitivity after resin composite class III restoration with flowable composite as liner - Dimyati, Andini; Sukartini, Endang; Aripin, Dudi (Universitas Padjadjaran, 2007)
Resin composites is one of the currently most frequently used aesthetic restoration material. A drawback of resin composites is contraction of polimerization which may result in the coming about of dental sensitivity due to microleakage. Flowable composite has high flow capacity and better adaptation capability making the thinnest application on cavity surfaces. An advantage of flowable composite is the possibility of using it as liner in composite resin restoration, which is expected to minimize the occurrence of post restoration dental sensitivity. This research was a descriptive research using the purposive sampling technique. The sample consisted of 27 first incisive and/or second incisive permanent maxilla teeth. A sensitivity test was used on the sample using chlor ethyl and completing questionnaire by patients. The result of dental sensitivity test indicated that 88.9% of the patients did not experience post restoration dental sensitivity and 11.1% of the patients was experience a decrease of dental sensitivity level. Based on research results the conclusion could be drawn that the used of flowable composite as a liner in resin composite class III restoration didn't had a post restoration dental sensitivity.